48.7k views
5 votes
Question 3 4 pts Solve the equation for the variable. Show your work and be sure to not forget to show all of your steps. -3(3 + 6b) = 36 - 3b​

User Kds
by
5.2k points

2 Answers

1 vote

Answer:

The value of b is -3.

Explanation:

The equation is,

→ -3(3 + 6b) = 36 - 3b

Now the value of b will be,

→ -3(3 + 6b) = 36 - 3b

→ -3(3) - 3(6b) = 36 - 3b

→ -9 - 18b = 36 - 3b

→ -18b + 3b = 36 + 9

→ -15b = 45

→ b = -(45/15)

→ [ b = -3 ]

Hence, the value of b is -3.

User Hamed Mayahian
by
5.4k points
5 votes

Answer:


\huge\boxed{\sf b = -3}

Explanation:

Given equation:

-3(3 + 6b) = 36 - 3b

Distribute

-9 - 18b = 36 - 3b

Add 3b to both sides

-18b + 3b - 9 = 36

-15b - 9 = 36

Add 9 to both sides

-15b = 36 + 9

-15b = 45

Divide -15 to both sides

b = 45/(-15)

b = -3


\rule[225]{225}{2}

User Hampus Nilsson
by
5.5k points